2020
DOI: 10.1021/acsnano.0c06830
|View full text |Cite
|
Sign up to set email alerts
|

Steering Effect of Bromine on Intermolecular Dehydrogenation Coupling of Poly(p-phenylene) on Cu(111)

Abstract: Among the multitudinous methodologies to steer on-surface reactions, less attention has been paid to the effect of externally introduced halogen atoms. Herein, highly selective trans-dehydrogenation coupling at the specific meta-C−H site of two poly(p-phenylene) molecules, p-quaterphenyl (Ph 4 ) and p-quinquephenyl (Ph 5 ), is achieved on Cu(111) by externally introduced bromine atoms. Scanning tunneling microscopy/ spectroscopy experiments reveal that the formed molecular assembly structure at a stoichiometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Lin et al 119 reported that the introduced Br atoms on Cu(111) promoted the selectivity toward the coupling reaction of pquaterphenyl (Ph 4 ) and p-quinquephenyl (Ph 5 ). The coassembly of the Br atoms and Ph 4 /Ph 5 with a specic ratio can efficiently increase their collision probability between two neighbouring Ph4 or Ph5 molecules (Fig.…”
Section: Interaction Between Supported Au and K Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al 119 reported that the introduced Br atoms on Cu(111) promoted the selectivity toward the coupling reaction of pquaterphenyl (Ph 4 ) and p-quinquephenyl (Ph 5 ). The coassembly of the Br atoms and Ph 4 /Ph 5 with a specic ratio can efficiently increase their collision probability between two neighbouring Ph4 or Ph5 molecules (Fig.…”
Section: Interaction Between Supported Au and K Atomsmentioning
confidence: 99%
“…(f) dI/ dV spectra sampled at the sites highlighted by the coloured dots in (e). Reproduced with permission (d-f) 119. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“… 34 Nevertheless, the role of the on-surface residue could be much more complicated as demonstrated in some recent works which present enhanced chemical selectivity with the assistance of leaving groups such as halogens. 35 , 36 …”
Section: Paradigm Of Programmable Ossmentioning
confidence: 99%
“…Various methods, including physical vapor deposition and solution-or interface-based methods, have been employed in fabricating low-dimensional organic materials such as individual crystals at nanometer or micrometer length scale [10][11][12][13][14], or two-dimensional (2D) organic thin films, which are important for many applications, including organic field-effect-transistors [5,8] and organic light-emitting diodes [9]. Generally, these methods can be grouped into two in terms of the interactions involved in the process.…”
Section: Introductionmentioning
confidence: 99%